PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY PERGURUAN TINGGI MELALUI PROGRAM BERBAGI AL-QUR’AN PADA TPA/TPSA IRSYADUNNAS KAMPUNG PARIT TANDIKEK BARAT - Risa Wahyuni EDT; Nurtati; Agusman; Alhazar Rinaldi; Muhammad Fadhil Al Amin; Reza Fadhillah; Nova Oktavia (Fakultas Ekonomi dan Bisnis Islam, 2025)
This community service activity aims to implement the concept of Corporate Social Responsibility (CSR) within the higher education environment through a social and religious program. The program was designed to strengthen the social role and moral responsibility of universities in supporting the community’s spiritual education. This activity employed a participatory approach involving lecturers and students from the Accounting Study Program at Universitas Sumatera Barat. The implementation consisted of several stages, namely the preparation, implementation, mentoring, and evaluation phases. The results of this activity indicate that CSR practices in the form of social and religious programs can enhance public trust and strengthen the university’s image as a socially responsible institution. Moreover, this activity provided direct benefits to the community by increasing access to Qur’an copies and supporting Islamic learning activities at local TPA/TPSA institutions. The program also fostered students’ awareness of social accountability and ethics in the field of accounting, aligning with the values of integrity, transparency, and empathy. This activity demonstrates that integrating CSR into community service programs can serve as an effective means of building sustainable relationships between higher education institutions and society.